The Board Duty to Comply with Good Corporate Governance Principles under the Australian and Indonesian Company Law - Tangkau, Daniel Julian (Business and Human Rights Law & Policy, 2025)
In the field of private economic activities, the formulation of a legal entity or a legal form chosen to run the business is a crucial part to be decided in the first place. In Indonesia, there are various forms of legal entity, such as sole trader, firm, commanditaire venootschap, limited liability corporation, and cooperation, in which the limited liability corporation is deemed as the most dominant form. Similarly, companies in Australia are dominated by limited liability corporations. In the light of setting up a company, the corporate governance aspect is an essential element that shall be highly upheld. This article compares the law on limited liability company in both Indonesia and Australia, as there is a significant difference in how both countries structuring the boards. The Indonesian company has two-tier boards: the board of directors and the board of commissioners, while the Australian company only has one, which comprises only the directors. Considering this difference, it is hypothetical that both systems have different approaches toward the compliance of corporate governance principles. This paper will discuss two issues: first, the overall comparison of board structure between Indonesian and Australian companies and the duty of the board. Second, discussion and criticism towards the compliance and implementation of corporate governance principles by each board system. It is notable that the company board system in both countries was formed by a long history of culture, politics, and law. Therefore, this paper aims not to make a simplistic conclusion of whether the one-board system in Indonesian companies is better than the two-board system in Australia or vice versa.